Regarding the Organization of Internal Control for Joint Activities - Zh. A. Kevorkova; N. G. Sapozhnikova (Учёт. Анализ. Аудит)
Joint activity is a specific activity of economic entities and agents, which requires constant monitoring of the implementation of such operations. The formation and disclosure of the information in the financial reporting statements regarding the joint activity is supported by regulatory legislation, however the application of IFRS in the activities of economic entities in disclosing this information requires the implementation of specific requirements that reveals the need for the development of information support (data back up) of such operations. The authors of the article reveal the problems that arise with information support of the internal control of the facts of economic life, undertaken in the framework of the execution of the contract of partnership. The proposed methodology for the implementation of the internal data control of the accounting entities will allow you to avoid significant mistakes. The formation of the systematic information on joint activity suggests and involves the determination of the accounting objects, documentation organization, registration and systematization of the facts of economic life, as well as the determination of control points. The determination of control points allowed the authors to generate information support for each of them and give recommendations on its application.